2000
DOI: 10.1177/000331970005100909
|View full text |Cite
|
Sign up to set email alerts
|

Criteria Predictive of Limb Viability at 1 Year in Patients with Chronic Severe Ischemia-TcPO 2 and Demographic Parameters

Abstract: Following an earlier study, the investigators sought to identify and define objective prognostic criteria of viability at 1 year of a limb with severe chronic ischemia. A study was undertaken in 116 patients (118 limbs) (74 men and 42 women), with a mean age of 71.9 years for men and 81.6 years for women. Static transcutaneous oxygen pressure (TcPO2) was measured with a verticalization sensitization test and inhalation of oxygen on JO and viability of the limb noted 1 year later. Logistic analysis was made of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…A potentially important point is the lack of precision in the exact location of the reference probe on the chest in the majority of studies that used this site [14, 15,22,26,27,[29][30][31][32]. However, Orenstein et al, investigated the variability of TcpO 2 measurements over 23 different locations in healthy volunteers (including above and below the nipple) [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A potentially important point is the lack of precision in the exact location of the reference probe on the chest in the majority of studies that used this site [14, 15,22,26,27,[29][30][31][32]. However, Orenstein et al, investigated the variability of TcpO 2 measurements over 23 different locations in healthy volunteers (including above and below the nipple) [33].…”
Section: Discussionmentioning
confidence: 99%
“…RPI should not be affected by age, and this could therefore be pertinent. However, Chomard et al, found there was no advantage in using RPI rather than TcpO 2 as an absolute value to predict limb viability at 1 year [31].…”
Section: Discussionmentioning
confidence: 99%